Analysis of P5RA Implementation of Merdeka Curriculum at MAN 4 Aceh Besar - Putra, Musiarifsyah; Habiburrahim; Buhori Muslim (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
This article analyzes the implementation of the Pancasila and Rahmatan lil Alamin (P5RA) Student Profile Strengthening Project at MAN 4 Aceh Besar within the framework of the Merdeka Curriculum. P5RA aims to form student characters based on Pancasila values and moderate religiosity. This research uses a descriptive qualitative approach with observation, interview, and document analysis methods. The results show that P5RA has successfully integrated Acehnese local wisdom values through the theme “Marriage Customs of Acehnese People,” although there are still challenges in managing time and supporting resources. The findings reinforce the importance of collaboration between teachers, students and external parties in supporting the success of P5RA.